Critical parameters of the delivery in Ten Pin bowling / Rizal Mohd Razman - Rizal, Mohd Razman (2013)
This exploratory study examined the possible important parameters for high level bowlers in three main areas - physical attribute, kinematics and movement variability. Consideration of the 'critical' parameters was made by looking at the variables that best distinguished the elite from the semi-elite bowlers using the discriminant function analysis. The study had an applied perspective in terms of the applications of the results and findings. Elite and semielite bowlers were grouped by their bowling score average (BSave), with participants scoring 200 pin falls and above assigned to the elite group. A total of 18 elite bowlers (M=10, F=8; BSave 213.2±6.80), 12 semi-elite bowlers (M=7, F=5; BSave 181.3±9.36) and 33 sedentary university students (M=14, F=19) representing the normal population were recruited. Ten anthropometric measurements and seven strength tests were conducted but there were no identifiable critical parameter of physical attributes for better bowlers as it was not possible to successfully distinguish between elite and semi-elite bowlers. However, differences were found when compared to the normal population, whereby the bowlers were heavier, had longer limbs, had stronger forearm internal rotation and arm flexion. A four-camera, 100 Hz, video-based 3D motion capture system was utilised for technique analysis. A total of 43 discrete kinematic variables were gathered from the motion analysis, out of which it was concluded that the two bowling groups had similar kinematic patterns for the majority of segments, with the exception of the shoulder and elbow regions. Discriminant analysis revealed that there were three critical kinematic variables, which showed an estimated 76.7% success rate for cross-validated classification in distinguishing the elite and semi-elite bowlers. From the discrete kinematic data, the within-subject inter-trial variability was also extracted to compare movement consistency. Consequently, 41 absolute variability variables were examined with a number of differences observed between the elite and semi-elite bowlers especially at the base (foot region) and the wrist, both of which are the most distal segments. The discriminant analysis highlighted four critical variability variables, with an estimated 76.7% success rate in distinguishing bowling playing level. It was concluded that the critical parameters of delivery for good bowling performance were faster shoulder velocity at front foot strike, faster elbow velocity at release, lower wrist height at release, more consistent foot lateral position at front foot strike, more consistent wrist lateral position at release, more varied foot slide distance, and more varied wrist superior-inferior position at release. Finally, as a consequence of the vast data gathered from this study, anthropometric and strength normative data, as well as kinematics and absolute variability measures for high level bowlers in Malaysia have been established and are readily available as a reference.